Pengaruh Promosi Dan Brand Image Terhadap Kepuasan Konsumen Pada Midori Japanese Restaurant Bintaro - Melly Agustin; Aldila Rahma Putri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of promotion and brand image on consumer satisfaction at Midori Japanese Restaurant Bintaro. The method used is the quantitative associative method. The population in this study were consumers of Midori Japanese Restaurant Bintaro with a total of 36,797 people in 2024. The sampling technique used was accidental sampling, with the Slovin formula technique, the research sample was 100 respondents. The data analysis method used in the study includes instrument testing consisting of validity testing, reliability testing, classical assumption testing consisting of normality testing, multicollinearity testing, heteroscedasticity and autocorrelation testing, multiple linear regression testing, correlation coefficients, hypothesis testing consisting of partial t-tests and simultaneous f-tests, and determination coefficient tests. From the results of this study, it is concluded that promotion has a positive and significant effect on consumer satisfaction with a T_count value> T_table (12.440> 1.985) and is reinforced with a significance value of 0.000 <0.05. Brand Image has a positive and significant influence on consumer satisfaction with a value of T_count > T_table (16.098 > 1.985) and is reinforced with a significance value of 0.000 < 0.05. Promotion and Brand Image have a positive and significant influence on consumer satisfaction with a value of F_count > F_table (134.624 > 3.090) and is reinforced with a significance value of 0.000 < 0.05 and the multiple linear regression equation is Y = 3.193 + 0.201 X1 + 0.731 X2 + α. The R-square value (determination coefficient) of 0.735 can be concluded that the promotion variables (X1) and brand image (X2) together have a contribution to the influence of the consumer satisfaction variable (Y) of 73.5% while the rest (100% -73.5%) is 26.5% influenced by other factors or variables not studied.